The Tree-Drawing Test (Koch’s Baum Test): A Useful Aid to Diagnose Cognitive Impairment - Michelangelo Stanzani Maserati; Corrado Matacena; Luisa Sambati; Federico Oppi; Roberto Poda; Maddalena De Matteis; Roberto Gallassi (Behavioural Neurology)
Objective. To study the Tree-Drawing Test in a group of demented patients and compare it with a group of mild cognitively impaired patients (MCI) and controls. Methods. Consecutive outpatients were classified as affected by dementia (Alzheimer’s disease (AD), frontotemporal dementia (FTD), and vascular dementia (VD)) or by MCI. Patients and controls underwent the Tree-Drawing Test and MMSE. Results. 118 AD, 19 FTD, 46 VD, and 132 MCI patients and 90 controls were enrolled. AD patients draw trees globally smaller than other patients and controls. FTD patients draw trees with a wider space occupation than AD and MCI patients but smaller than controls as well as VD patients. Trees drawn by MCI patients are intermediate in size between AD patients and controls. The trunk-to-crown ratio of trees drawn by cognitive impaired patients is greater than controls while the tree size-relative-to-page space index is significantly smaller. The tree size-relative-to-page space index of trees drawn by AD patients is smaller than that of the other cognitively impaired patients. Tree height and the trunk-to-crown ratio are independent predictors of cognitive impairment. Conclusions. Trees drawn by cognitively impaired patients are different from those drawn by healthy subjects with a progressive differentiation from mild to more relevant degrees of cognitive impairment.